The Concentration of Hospital‐Based Medical Spending: Evidence from Canada1. (September 2016) - Côté‐Sergent, Aurélie; Échevin, Damien; Michaud, Pierre‐Carl
Abstract: In this paper, we present evidence on the concentration of hospital‐based medical spending in Canada. We use longitudinal administrative data from the province of Quebec to document how medical spending is concentrated cross‐sectionally, over time and near the end of life when death occurs in hospital. Average expenditures rise rapidly with age, starting around the age of 50, and are concentrated in a small fraction of high‐cost users. For example, the top 1 per cent of men and women in terms of hospital spending account for 52.9 per cent and 49.8 per cent of total spending respectively. Persistence among high users is quite low. Fewer than 19.7 per cent of those in the top quintile of hospital spending stay in the same quintile the following year. Finally, hospital spending among those in their last year of life and who die in hospital can account for 11.3 per cent of total hospital spending in the population.